Performance measurement in Spanish local governments. A cross-case comparison study - Torres, Lourdes; Yetano, Ana; Pina, Vicente (2011)
This paper explores local government in Spain: the nature of and extent to which performance measures are delvoped and how they are used in sonme of the biggest Spanish local gvernments. The features of perfornmance measurement in Spain raise the question of why non-mandatory performance indicators are introduced and why specific initiatives are undertaken. A cross-theory strategy allows us to build a wider explanation of the cases studied. This study shows that performance measurment systems are not neutral but conditioned by the environmental context of each local government to fit int its organizational sturcture. Spanish local governments are experimenting with different approaches - centralized / decentralized, top-down / bottom-up, internal / external usen - to implement performance measures. A relationship between external use and the top-down approach, and internal use and the bottom-up approach can be found. Our results also show that the institutional image value of taking decisions under rational decision-making models is the primary driver of implementation processes. - Reproduced.
Keywords: Performance appraisal - Spain; Local government - Spain; Local government